MATERI BAHAN AJAR MATAKULIAH BAHASA INDONESIA UNTUK PROGRAM STUDI ILMU HUKUM - Suhardi Suhardi; Sendi Triwilopo; D. Novrian Syahputra (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
This article describes the results of research on the needs analysis of Indonesian language subject matter in the Bachelor of Law Studies Programs. This research is a qualitative research with a descriptive approach. Data collection is done by interviews and data processing carried out by steps, reduction, classification, and drawing conclusions. The results of the study showed that the teaching materials in Indonesian subjects majoring in law included material about (1) reading with analysis to find out ideas or reading ideas and assessing reading material, (3) describing an event that had legal aspects in an objective form, (4) writing scientific work, (5) listening, and (6) speaking scientifically. This study also recommends adjusting the syllabus for Indonesian language courses.